Development of Petanque Sport in Central Java Province - Witri Suwanto; Agus Kristiyanto; Muchsin Doewes (Kazimierz Wielki University, 2018)
Background: The background of this research is Central Java as one of the provinces in Indonesia is an area that has considerable sports potential. Various sport accomplishment that has been achieved by Indonesia is contributed by athletes from Central Java province. Petanque Sport is one of the new sports branch in Central Java. Petanque sport comes France. The purposes of this research are to study: 1) petanque sport socialization efforts in Central Java, 2) community groups who become petanque Sport actors in Central Java. Subject and Method: This research was conducted in Federation of petanque Indonesia (FOPI) Central Java. This research is a qualitative research that is interpretative, and presented using descriptive approach. We made observations, analyzed documents, and conducted some interviews to collect our data. Result: The results in this study are as follows. 1) Petanque Sport is one of the fastest growing sport branches in Central Java since 2016. Petanque Sport is one of sport branches that has been growing fast in Central Java since 2016.The socialization efforts, which were conducted by Central Java for two years, has succeeded in establishing several organizations at the district level. The socialization efforts, which has been conducted by Central Java for two years has succeeded in establishing several organizations at district level. 2) The community target in petanque sport socialization are teachers, college students, students and the general public. Conclusion: The socialization that has been conducted by FOPI Central Java for two years has given a satisfactory result. Recorded in the beginning of 2018, there are 21 organizations formed from 35 districts which play an active role in developing athletes at the district level. Work performance and teamwork of the board are the key to success in socializing petanque sport in Central Java.